KEPASTIAN HUKUM PEMENUHAN HAK KREDITOR DALAM EKSEKUSI OBJEK JAMINAN HAK TANGGUNGAN MELALUI PARATE EKSEKUSI - Deasy Soeikromo (Universitas Muhammadiyah Sumatera Utara, 2016)
By the existing Law Number 4 of 1996 concerning Land Mortgage has given a chance to creditor to sell all assets which is collateralized by debtor without court process. This thing happens to avoid “litigation adjudication” which is taken long time for finishing the problem. Because of that, when debtor fails to fulfill the obligation (wanprestasi), so the creditor party does not need to sue the debtor, but through “execution parate” which is known before as State Auction Service Office to be auctioned in public. Parate executie ruled in Law Number 4 of 1996 concerning Land Mortgage aimed to creditor gains easily the credit from debtor who fails to fulfill the obligation. At the time, creditor could sell the object of land mortgage without court decision. However this way does not used for some creditors because the confusion the regulation it self about parate executie in Law Number 4 of 1996 concerning Land Mortgage.